Effects of ramp width variation on the hydraulic conditions of spillway that affect downstream migrating fish - Seyed Sobhan Aleyasin; Sedem Kumahor; Mark Francis Tachie; Christos Katopodis; Haitham Ghamry (Scientific Reports)
Abstract An experimental investigation was conducted to elucidate the effects of a 45º upstream spillway ramp with varying spanwise width ratios (10%, 25%, 50%) on the turbulent flow characteristics used to guide fish downstream. A particle image velocimetry system was employed to acquire the velocity field in several vertical and spanwise planes and analyze various statistics including mean velocities, spatial velocity gradient, Reynolds stresses and turbulent kinetic energy. The results indicate that the flow topology depends significantly on the ramp width ratio. However, regardless of the width ratio, a recirculation region was observed near the foot of the spillway and a smaller one formed upstream of the ramp. For the 10% ramp width ratio, the smaller recirculation bubble accompanied by the lower velocity, spatial velocity gradient and turbulent kinetic energy along the test channel generate a more favorable pathway for downstream migrating fish. Although a partial-width ramp (i.e., 10% width ratio) is less costly and easier to retrofit compared to a full-width ramp, it creates some spanwise inhomogeneity which may impact the migration route and time of some fish species, particularly those that swim close to the riverbed.